Information systems planning in selected libraries in the Philippines - Alipis, Ferdinand Angelo M. (2000)
This study was an investigation and documentation of the information systems planning experiences of the selected libraries in the Philippines. It involved four selected types of libraries namely, the National Library (public library), the International Rice Research Institute Library (special library), the Rizal Library of the Ateneo de Manila University (academic library), and the Immaculate Conception Academy High School Library (school library), Greenhills, San Juan Metro-Manila.